Preliminary Studies on Air-layering on Deodar Cedrus deodara - Chandra, J. P.; Sharma, R. K. (Indian Forester, 1974)
Results of a trial conducted on air-layering of deodar branches are reported. The application of Seradix B3 induced rooting and 28 percent of the air-layers rooted while air-layers without the application of Seradix did not root.